Visual Representation of Safety Cases - Jennifer Brain (Measurement + Control, 2012)
Historically, safety cases in the nuclear industry have tended to follow a visually similar approach; descriptive text using a (gradually evolving) template driven in part by a desire to minimise the scope of changes to legacy safety cases. However, a number of recent factors are beginning to challenge this approach. Academic work and developments in other industries are proposing new structured and diagrammatic techniques and tools such as Claims-Arguments-Evidence and Goal Structured Notation. Additionally, new build projects are offering a ‘clean-sheet’ and an opportunity to break away from a traditional safety case presentation. This paper introduces a number of techniques for representing a safety case and identifies some of the considerations for selecting a presentation. It then presents the Claims-Arguments-Evidence approach proposed to support the C&I safety case for new build in order to describe some real life experience.